Reporte de virosis en el germoplasma de ñame (Dioscorea spp.) en Cuba - Hernandez Perez, R.=700 1 Herrera Isla, L.; Gonzalez, J.; Sanchez, I.; Garcia, J.
(Es, En)
Ilus., 17 ref.
Keywords: DIOSCOREA; VIRUS; POTYVIRUS; SINTOMAS; CUBA; ÑAME